"His main platform is 'stop the turbines' ": Political discourse, partisanship and local responses to wind energy in Canada. (December 2018) - Walker, Chad; Stephenson, Laura; Baxter, Jamie
Abstract: Decades after wind energy has taken hold in many developed countries, social scientists are beginning to understand the complex story of what causes differentiated responses to local development. Transitions in this literature include moving from attitudinal factors, and the infamous Not in My Backyard (NIMBY) explanation, toward place attachment, environmental justice, and how policy development might shape support for wind turbines in rural communities. While this research has advanced our understanding of some of the major questions in this area, the political arena has largely remained implicit or in the background, rather than a specific area of detailed inquiry. Addressing this gap in the literature, we detail findings from our mixed method study of interviews (n = 54) and surveys (n = 240) with local residents, developers, and other stakeholders in Ontario and Nova Scotia, Canada. We focus on the interplay of partisanship and geography, and how together they can powerfully influence attitudes toward wind energy. Specifically, we extend the existing literature and argue that when parties politicize the issue of wind energy — especially within the context of an urban/rural divide — it becomes intertwined with elements of ideology which can amplify responses and further entrench local conflict. Highlights: Using mixed methods, we study partisanship and support for wind energy in Canada. Differences between Ontario and Nova Scotia may be attributed to political context. High levels of local support in Nova Scotia associated with a political consensus. Increasing support will require better understanding of ideological messaging. Future work should examine trends in other places and through larger data sets.